Construction of a novel gene signature linked to ferroptosis in pediatric sepsis - Fan, Mingyuan; Chen, Meiting; Gao, Yongqi; Jiang, Huilin; Li, Yanling; Zhu, Gongxu; Chen, Shengkuan; Xu, Yiming; Chen, Xiaohui (Frontiers in Cell and Developmental Biology, 2025)
IntroductionPediatric sepsis is a complex and life-threatening condition characterized by organ failure due to an uncontrolled immune response to infection. Recent studies suggest that ferroptosis, a newly identified form of programmed cell death, may play a role in sepsis progression. However, the specific mechanisms of ferroptosis in pediatric sepsis remain unclear.MethodsIn this study, we analyzed microarray datasets from pediatric sepsis and healthy blood samples to identify ferroptosis-associated genes. A protein-protein interaction (PPI) network analysis and histological validation were performed to identify key genes. Additionally, immune infiltration analysis was conducted to explore the correlation between immune cells, immune checkpoint-related genes, and key genes. A competing endogenous RNA (ceRNA) network was constructed to investigate potential regulatory mechanisms involving long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and key ferroptosis-related genes.ResultsWe identified 74 genes associated with ferroptosis in pediatric sepsis. Among them, five key genes (MAPK3, MAPK8, PPARG, PTEN, and STAT3) were confirmed through PPI network analysis and histological validation. Immune infiltration analysis revealed significant interactions between immune cells and key genes. The ceRNA network provided insights into the regulatory relationships between lncRNAs, miRNAs, and ferroptosis-related genes.DiscussionThese findings enhance our understanding of the role of ferroptosis in pediatric sepsis and highlight potential therapeutic targets for future research and clinical interventions.